A new precursor for fabricating TiN coating on 316L stainless steel at low temperature without corrosive byproducts. Issue 15 (15th October 2019) - Song, Miao; Yang, Yafeng; Guo, Junjie; Xiang, Maoqiao; Zhu, Qingshan; Ge, Yu
Abstract: High quality TiN coated 316L stainless steel can hardly be fabricated by the traditional chemical vapor deposition (CVD) methods because of the formation of HCl (g) corrosive byproduct and phase transformation at high deposition temperature. To address the problem, herein, for the first time a novel TiCl2 precursor is proposed to fabricate TiN coating on 316L substrate in N2 atmosphere at low temperature. The idea is based on that metastable TiCl2 can release fresh Ti atoms by its disproportionation reaction, and then the fresh Ti atoms react easily with N2 to form TiN coating at low temperature without HCl byproduct. The reaction path, interface reaction, and performance of the TiN coating were investigated. The optimized nanograin TiN (45 nm) coating was successfully fabricated on 316L at 750 °C and it exhibited excellent corrosion resistance.